2006
DOI: 10.1007/s10350-006-0511-8
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin for the Treatment of Severe, Refractory, and Recurrent Clostridium difficile Diarrhea

Abstract: Intravenous immunoglobulin may be effective for severe, refractory, or recurrent Clostridium difficile diarrhea after failed conventional treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(81 citation statements)
references
References 20 publications
1
78
0
2
Order By: Relevance
“…Toxinreactive IgG and IgA can be detected in the intestine and serum and have the potential to block toxin binding to epithelial receptors and promote toxin clearance from the intestine (71). The presence of antibodies that are reactive to C. difficile TcdA has been positively correlated with asymptomatic carriage of C. difficile (32), although there are conflicting reports regarding whether naturally occurring antitoxin antibodies and intravenous immunoglobulin therapy (IVIG) affect the disease course (32,69,70,(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83). Questions thus remain as to the extent to which antibody levels may confer protection against CDI.…”
Section: Risk Factors For Developing CDImentioning
confidence: 99%
“…Toxinreactive IgG and IgA can be detected in the intestine and serum and have the potential to block toxin binding to epithelial receptors and promote toxin clearance from the intestine (71). The presence of antibodies that are reactive to C. difficile TcdA has been positively correlated with asymptomatic carriage of C. difficile (32), although there are conflicting reports regarding whether naturally occurring antitoxin antibodies and intravenous immunoglobulin therapy (IVIG) affect the disease course (32,69,70,(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83). Questions thus remain as to the extent to which antibody levels may confer protection against CDI.…”
Section: Risk Factors For Developing CDImentioning
confidence: 99%
“…Other approaches attempting to treat refractory CDI have included the use of intravenous immunoglobulin (IVIG) administration, pulsed and tapering doses of vancomycin, vancomycin plus rifampin, probiotics (lactobacilli and Saccharomyces boulardii) and a C. difficile toxoid vaccine. 17,23,91,130,[132][133][134][135][136] Another successful approach appears to be the use of fecal transplants. This procedure involves the reconstitution of patient gut flora from a donor sample, usually administered via nasogastric tube.…”
Section: Interventions and Future Studiesmentioning
confidence: 99%
“…There are several reported cases of successful treatment with intravenous tigecycline, alone or in combination with vancomycin [3]. Other authors demonstrated that intravenous immunoglobulins might also contribute to the improvement of these patients if given in addition to oral vancomycin [4].…”
Section: Discussionmentioning
confidence: 99%
“…Despite existing guidelines, there is no defined protocol for treating severe refractory CDI, and literature data comes from individual case reports with different treatment approaches. Intravenous tygecyclin, intravenous immunoglobulins, oral vancomycin in higher doses, and vancomycin enema are some of the suggested treatment regimens but they were all applied to a small number of patients [3][4][5][6]. Oral teicoplanin is another antibiotic, which was proven to be successful in the treatment of patients with CDI, including those with severe disease [7,8].…”
Section: Introductionmentioning
confidence: 99%